ANALISIS KEPUTUSAN PEMBELIAN TIKET PESAWAT SECARA ONLINE (STUDI KASUS RUTE PENERBANGAN PALEMBANG – CENGKARENG) - Idayanti Idayanti; Fakhry Zamzam; Luis Marnisah (Integritas Jurnal Manajemen Profesional (IJMPRO), 2021)
This study aims to analyze the influence of product, price, promotion, place, people, physical evidence, and the process, or what is known as the 7P marketing mix on the decision to purchase plane tickets Online. The methodology used in this study is multiple linear regression analysis method, with the population used in this study consisting of 3 (three) airlines, namely Sriwijaya Air, Batik Air, and Lion Air Palembang with 329 respondents and processed with SPSS version 22. Partially, the marketing mix variables that influence the purchasing decisions to purchase plane ticket online of Palembang are price, place, and process. The conclusion of this study, the results of the analysis show that the product, price, promotion, place, people, physical evidence, and process variables together have a positive and significant effect on the purchasing decision to purchase plane tickets Online of the Palembang city with an F value of 64.908 and an r2 value of 0.766 or 76% and the rest is influenced by other factors.